Language and time - Smith, Quentin, 1952- (Oxford University Press, 2002)
This book offers a defense of the tensed theory of time, a critique of the New Theory of Reference, and an argument that simultaneity is absolute. Although Smith rejects ordinary language philosophy, he shows how it is possible to argue from the nature of language to the nature of reality. Specifically, he argues that semantic properties of tensed sentences are best explained by the hypothesis that they ascribe to events temporal properties of futurity, presentness, or pastness and do not merely ascribe relations of earlier than or simultaneity. He criticizes the New Theory of Reference, which.